PENGARUH MODEL PROBLEM BASED LEARNING DENGAN MEDIA POSTER UNTUK MENINGKATKAN PEMAHAMAN DAN KEMANDIRIAN PESERTA DIDIK MUATAN PELAJARAN MATEMATIKA SEKOLAH DASAR - Abdussalam; Siska Pratiwi; Yunita Hariyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the difference in the influence of Problem Based Learning with poster media on the understanding and independence of class V students at UPTD SDN Gili Timur 1. Based on the output obtained sig 0.000 < 0.05 so it can be concluded that this shows that there is an average difference between research subjects and using the Problem Based Learning learning model using posters for Understanding and Independence. This is proven by the results of students' test questions regarding spatial shapes which were obtained based on the output that had been tested. It was obtained that the data description had an average mean at pre of 6.58 while the post data was 8.92. Meanwhile, based on the output that has been tested for independence, the data description shows that there is an average mean in the pretest of 49.58 while the posttest data is 53.75. So there is a difference in the influence of Problem Based Learning with poster media on the understanding and independence of class V students at UPTD SDN Gili Timur 1.